2021
DOI: 10.1144/geochem2021-015
|View full text |Cite
|
Sign up to set email alerts
|

Near real-time management of spectral interferences with portable X-ray fluorescence spectrometers: application to Sc quantification in nickeliferous laterite ores

Abstract: Since the development of portable XRF (pXRF) spectrometers, few studies have been conducted on the influence of spectral interferences between chemical elements. This study aims to improve the management of these interferences to obtain more reliable geochemical analyses. We specifically investigate Ca-related interferences on Sc analysis for the case of Ni-rich laterite samples using the Niton XL3t GOLDD+ pXRF analyser. Three quantification methods were tested on 59 pelletised samples using the ‘Soil’ mode. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Once verified, deposit-scale Sc-Al 2 O 3 correlations may first prove useful to estimate Sc concentrations on surface outcrops or pit walls using portable devices such as pXRF. Indeed, the relatively low Sc concentrations observed in Ni-laterites (<100 ppm) limit the use of pXRF to directly assess Sc [51], whereas Al concentrations, typically about a few wt%, can be confidently estimated using such a device. The slightly lower accuracy obtained on Al analysis from pXRF than from a classical assay analysis would only marginally affect the estimation of Sc.…”
Section: Implications For the Assessment Of Sc In Ni-lateritesmentioning
confidence: 99%
“…Once verified, deposit-scale Sc-Al 2 O 3 correlations may first prove useful to estimate Sc concentrations on surface outcrops or pit walls using portable devices such as pXRF. Indeed, the relatively low Sc concentrations observed in Ni-laterites (<100 ppm) limit the use of pXRF to directly assess Sc [51], whereas Al concentrations, typically about a few wt%, can be confidently estimated using such a device. The slightly lower accuracy obtained on Al analysis from pXRF than from a classical assay analysis would only marginally affect the estimation of Sc.…”
Section: Implications For the Assessment Of Sc In Ni-lateritesmentioning
confidence: 99%
“…The first two principal dimensions CCA1 and CCA2 explained 35.9% and 18.5 % of the total variance, respectively. A positive correlation was observed between sand and Cu, Zn, As, Pb, and Fe; clay and Al, V, and Ni; Silt and Al, Ni, and V. Here, one is expecting Cr to be positively correlated to soil texture ( Kim & Dixon, 2002 ; Lacroix et al, 2021 ; Rudzionis et al, 2022 ), however, due to high Fe concentration, the pXRF efficiency in reporting the actual amount of Cr declines due to a lower absorption edge in energy than the fluorescent peak of Fe (EPA, 2007). Such an effect can be corrected mathematically using fundamental parameter coefficients related to particle size and matrix effects.…”
Section: Discussionmentioning
confidence: 98%
“…V. Here, one is expecting Cr to be positively correlated to soil texture (Kim & Dixon, 2002;Lacroix et al, 2021;Rudzionis et al, 2022), however, due to high Fe concentration, the pXRF efficiency in reporting the actual amount of Cr declines due to a lower absorption edge in energy than the fluorescent peak of Fe (EPA, 2007). Such an effect can be corrected mathematically using fundamental parameter coefficients related to particle size and matrix effects.…”
Section: Challenges Associated With Select Soil Properties and The Pxrfmentioning
confidence: 99%
“…Moreover, the period of intense weathering is not yet constrained. Although the formation of Ni laterite deposits have been linked to climate change [113], there is no clear relationship between the present climate and the ore type, grade, or size of Ni(Co) laterite deposits from this region. It should be of interest to constrain whether or not some localities have undergone cold month mean temperatures of 15-27 • C or warm month mean temperatures of 22-31 • C [114].…”
Section: Research Perspectivesmentioning
confidence: 99%
“…In addition to Ni ore and economic contents of Co, the Ni(Co) laterite deposits host critical metals or high-tech elements that are increasingly demanded by many industries. These deposits are becoming worth targets for Sc, REE, and PGE [94,[113][114][115][116][117]. Recent studies have shown that Ni(Co) laterite deposits from the Caribbean, Balkan, and Pacific regions are enriched in critical metals (e.g., REE, PGE, and Sc) that could be economically extractable [94,[116][117][118].…”
Section: Research Perspectivesmentioning
confidence: 99%